Original paper Effect of a urinary catheter on seed position and rectal and bladder doses in CT-based post-implant dosimetry for prostate cancer brachytherapy - Kunogi, Hiroaki; Yamaguchi, Nanae; Wakumoto, Yoshiaki; Sasai, Keisuke (Journal of Contemporary Brachytherapy, 2015)
Purpose: To assess the variability in rectal and bladder dosimetric parameters determined according to post-implant computed tomography (CT) images in patients with or without a urethral catheter. Material and methods: Patients with prostate cancer who were scheduled to undergo CT after brachytherapy between October 2012 and January 2014 were included. We obtained CT series with and without a urinary catheter in each patient. We compared the rectal and bladder doses in 18 patients on each CT series. Results: The shifts in the seed positions between with and without a catheter in place were 1.3 ± 0.3 mm (mean ± standard deviation). The radiation doses to the rectum, as determined on the CT series, with a urethral catheter were higher than those on CT without a catheter (p < 0.001). Radiation doses to the bladder with a catheter were significantly lower than those without a catheter (p = 0.027). Conclusions: Post-implant dosimetry (PID) with no catheter showed significantly lower rectal doses and higher bladder doses than those of PID with a catheter. We recommend the PID procedure for CT images in patients without a catheter. Use of CT with a catheter is limited to identifying urethral position.